Method for extracting lithium from brine containing sulfate radicals

The method addresses lithium extraction from sulfate-containing brines by adjusting pH and using chloride salts to replace sulfate ions, enhancing adsorbent performance and reducing costs and environmental impact, achieving efficient lithium extraction and high yield.

CN119240756APending Publication Date: 2025-01-03HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411378425.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing lithium extraction methods from sulfate-containing brines face challenges such as high energy consumption, environmental pollution, and reduced yield due to the deactivation of aluminum-based adsorbents by sulfate and carbonate ions, and the need for additional chemicals like acids and salts, which increase costs and environmental impact.

Method used

A method involving pH adjustment of brine to 5-7, using aluminum-based lithium adsorbents, followed by chloride salt replacement of sulfate ions, and a membrane system for impurity removal and lithium precipitation, with recycling of materials to reduce costs and environmental impact.

Benefits of technology

The method effectively extracts lithium with reduced performance degradation of adsorbents, lowers operational costs, and minimizes environmental pollution by recycling materials, achieving battery-grade lithium carbonate yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069268830000041
    Figure BDA0005069268830000041
  • Figure BDA0005069268830000042
    Figure BDA0005069268830000042
  • Figure BDA0005069268830000051
    Figure BDA0005069268830000051
Patent Text Reader

Abstract

The invention discloses a method for extracting lithium from brine containing sulfate radicals. The method comprises the following steps: S1, selecting brine containing sulfate radicals, filtering to remove impurities, and adjusting the pH value to 5-7; s2, enabling the brine to pass through a resin column containing an aluminum-based lithium adsorbent, and extracting lithium ions; s3, leaching the aluminum-based lithium adsorbent with water, performing countercurrent analysis, and collecting an analyzed lithium-containing liquid A; repeating the steps S2 and S3 until the adsorption capacity of the aluminum-based lithium adsorbent is reduced to 70% or below of the initial capacity; s4, soluble chlorate is used for carrying out salt top material replacement on sulfate radicals mixed in the aluminum-based lithium adsorbent, pure water analysis is carried out, and analyzed lithium-containing liquid B is obtained; and combining and analyzing the lithium-containing liquid. According to the method, the problem of performance degradation of the aluminum-based lithium adsorbent in the process of extracting the lithium from the brine containing the sulfate radicals is solved in a manner of adjusting the pH value in the front stage and replacing the sulfate radicals with the chlorine radical jacking material after adsorption, and various materials in the system can be basically recycled, so that the operation cost is fundamentally reduced, and meanwhile, the environmental protection problem caused by introduction of a large amount of salt is completely eradicated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium extraction from salt lakes and ores, and particularly relates to a method for extracting lithium from brine containing sulfate. Background Art

[0002] As the lightest element among all known metals, lithium metal has been widely used in new energy, ceramics, medicine, metallurgy, 3C and other industries, and its status is similar to the existence of Middle Eastern oil. With the acceleration of the modernization process, the era of traditional oil has come to an end, and the era of new energy is about to come, and the arrival of new energy is inseparable from the support of lithium resources. Therefore, the exploitation of lithium resources is particularly urgent. At present, the world's proven lithium resource reserves are about 89 million tons, of which ore lithium resources account for 40% and salt lake lithium resources account for 60%. Although salt lake lithium resources are richer than ore lithium resources, most of the lithium resource mining currently comes from ore lithium extraction, and the production capacity released by salt lake lithium extraction is quite limited. This is mainly due to the high technical barriers of salt lake lithium extraction. Not all types of salt lakes can be used for lithium extraction using low-cost process methods. The sulfate roasting method, sulfuric acid roasting method, and chloride salt roasting method used in traditional ore lithium extraction not only have high energy consumption and cost, but also produce great pollution. Therefore, the continuous breakthrough and improvement of salt lake and ore lithium extraction technology will become the direction of countries' efforts.

[0003] In the existing lithium extraction technology, the adsorption method using aluminum-based adsorbents has become a more common industrial method, but due to the differences in the influencing ions and pH of various lithium-containing brines, the deactivation of aluminum-based adsorbents in the adsorption method often occurs, especially the carbonate, sulfate and pH contained in the brine, which have the greatest impact on the performance of aluminum-based adsorbents. For this reason, for brine containing sulfate, patent CN115814465A uses a salt solution after adding a weak acid to activate the adsorbent, but the method does not explain the post-treatment of the acidified salt solution. In this way, the introduction of the acidified salt solution not only causes an increase in material costs, but also the large-scale use of acids, salts and other substances will bring certain pressures to the environment. Patent CN116282087A uses a nanofiltration forward process to reduce the sulfate concentration to a suitable range, and then proceeds in accordance with the method of extracting lithium from a chloride salt lake, but adding a nanofiltration forward section not only increases the industrialization cost, but also reduces the yield of battery-grade lithium carbonate due to the increased nanofiltration forward section. Summary of the invention

[0004] In view of the defects in the prior art, the present invention provides a method for extracting lithium from sulfate-containing brine.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for extracting lithium from sulfate-containing brine comprises the following steps:

[0007] Step S1. Selecting brine containing sulfate, filtering and removing impurities to obtain brine with a pH value of 5 to 7, or adjusting the pH value to 5 to 7 with acid or alkali;

[0008] Step S2. adding the brine treated in step S1 to a resin column containing an aluminum-based lithium adsorbent to perform column adsorption to extract lithium ions from the brine;

[0009] Step S3. After the adsorption is completed, the aluminum-based lithium adsorbent after the lithium extraction in step S2 is eluted with pure water (water top material), countercurrent analyzed, and the lithium-containing liquid A is collected and analyzed;

[0010] Repeating steps S2 and S3 until the adsorption capacity of the aluminum-based lithium adsorbent drops to 70% or less of the initial capacity;

[0011] Step S4. using soluble chloride salt to replace sulfate ions contained in the aluminum-based lithium adsorbent after lithium extraction, and then analyzing with pure water to obtain an analyzed lithium-containing liquid B; combining the analyzed lithium-containing liquid A and the analyzed lithium-containing liquid B to obtain a mixed analyzed lithium-containing liquid.

[0012] The above method further comprises the following step S5: removing impurities and RO concentration from the mixed analytical lithium-containing liquid by using a membrane combination and a resin system, and then performing MVR and lithium precipitation treatment to obtain lithium carbonate with a main content reaching battery grade.

[0013] The above method further includes the following step S6: removing sulfate from the salt top material replacement liquid containing sulfate obtained in the step S4 through a strong base anion exchange resin, and then collecting the chloride-containing replacement liquid after the sulfate is removed for recycling to replace the sulfate on the next batch of deactivated aluminum-based lithium adsorbent.

[0014] The method of the present invention is aimed at extracting lithium from brine with a high sulfate content. The pH value is adjusted to a suitable range of 5 to 7 by using an acid or alkali in the front stage, and the chloride is used to replace the sulfate after adsorption. This overcomes the problem of performance degradation of aluminum-based lithium adsorbents in extracting lithium from brine containing sulfate. Various materials in the system can basically be recycled, which fundamentally reduces the operating cost and prevents the occurrence of environmental problems caused by the introduction of a large amount of salt.

[0015] Furthermore, in step S1, the brine containing sulfate may be salt lake brine containing sulfate and / or ore leaching brine containing sulfate.

[0016] Furthermore, in step S1, the method of the present invention can be adopted when the mass concentration of sulfate contained in the brine is 6% to 50% of the mass concentration of chloride ions. However, when the mass concentration of sulfate accounts for less than 6% of the mass concentration of chloride ions, the aluminum-based lithium adsorbent will not produce sulfate poisoning during the process of adsorption and lithium extraction. When the mass concentration of sulfate accounts for more than 50% of the mass concentration of chloride ions, the aluminum-based lithium adsorbent is severely blocked and poisoned by sulfate, and a large amount of chloride salt is required for replacement, which generates extremely high costs and is not conducive to industrialization.

[0017] If the pH of the sulfate-containing brine is within the range of 5 to 7, it has limited effect on the performance of the aluminum-based adsorbent, and there is no need to add acid or alkali to adjust the pH in the previous stage.

[0018] Furthermore, in step S1, the filtration and impurity removal adopts a multi-media filtration method, and the multi-media used includes quartz sand, ceramic membrane, hollow fiber membrane, etc. After impurity removal, the purpose of adjusting the pH with acid or alkali is to remove carbonate or adjust the pH to a range of 5 to 7 to eliminate the effect on the performance attenuation of the aluminum-based lithium adsorbent.

[0019] Furthermore, in step S2, the aluminum-based lithium adsorbent can be selected from at least one of the following: the aluminum-based lithium adsorbent prepared in patent CN113578252B, the aluminum-based lithium adsorbent used for extracting lithium from lithium-containing brine prepared in patent CN106622103B, or an aluminum-based lithium adsorbent with similar characteristics on the market.

[0020] Furthermore, in step S2, the aluminum-based lithium adsorbent needs to be activated before use, and the activation method is as follows: flushing through the column with deionized water until the lithium ion content at the outlet of the resin column containing the aluminum-based lithium adsorbent reaches the activation end point within 20 ppm.

[0021] Furthermore, in step S2, the adsorption is completed when the lithium content of the tail liquid at the outlet is measured to a lithium retention rate of less than 50%. The retention rate refers to the mass concentration of lithium contained in the tail liquid after the pretreated raw halogen passes through the aluminum-based lithium adsorption column, which accounts for the mass concentration of lithium contained in the tail liquid before the raw halogen enters the column.

[0022] Furthermore, in step S4, the soluble chloride salt is selected from: one or a mixture of magnesium chloride, sodium chloride, lithium chloride, potassium chloride.

[0023] Furthermore, in step S4, the soluble chloride salt is used in the form of an aqueous solution, and the mass concentration of the soluble chloride salt is between 6% and 26.5%. The lower the mass concentration of the soluble chloride salt, the greater the amount used.

[0024] Furthermore, the membrane combination in step S5 can be selected from at least two of the following membranes for membrane combination treatment: hollow fiber membrane, ceramic membrane, nanofiltration membrane, RO reverse osmosis membrane, bipolar membrane electrodialysis; the resin can be selected from at least one of the following resins: calcium and magnesium chelating resin, and chelating resin specifically for boron removal.

[0025] Furthermore, after the lithium precipitation treatment in step S5, the steps of suction filtration, pulp washing, leaching, drying and powdering are also included.

[0026] Furthermore, when the aluminum-based lithium adsorbent in step S2 adsorbs lithium ions in the brine, it is easily affected by sulfate, carbonate, and acidic water environment with a pH value of less than 5 in the brine and becomes inactivated. The carbonate has been removed by adjusting the pH value of the original halide acid in the early stage of adsorption, and the sulfate is replaced and removed by chloride top material in step S3 after the adsorption is completed. The acidic brine water quality of the ore leaching is adjusted by alkali to eliminate the influence on the crystal form of the aluminum-based lithium adsorbent.

[0027] Furthermore, after the soluble chloride salt in step S4 displaces the sulfate in the aluminum-based lithium adsorbent, the tail liquid is a mixture of chloride salt and a small amount of sulfate. After the mixture is treated with a strong base quaternary ammonium salt anion exchange resin to remove sulfate, it can be recycled without adding new salt solution.

[0028] Furthermore, the strong base anion exchange resin described in step S6 is a strong base quaternary ammonium salt anion exchange resin, which needs to be converted into a chlorine form and activated by hydrochloric acid with a mass concentration of 4% before use, and then washed with pure water until the pH value of the water outlet is close to neutral before use.

[0029] It should be noted that the aluminum-based lithium adsorbent, the chelating resin for boron removal, the chelating resin for calcium and magnesium removal, etc. mentioned in the present invention, when applied in projects, are often carried out in a single column or multiple columns in series or parallel. Further, continuous ion exchange technology can be used, such as a mixed simulated bed system or a turntable simulated moving bed, depending on the specific working conditions.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The present invention can reduce the influence of carbonate and too low pH on the performance attenuation of aluminum-based lithium adsorbent by adjusting the pH of the original brine to 5-7. If the pH value of the original brine is in the range of 5 to 7, the acid adjustment step can be omitted, and the aluminum-based lithium adsorbent lithium extraction system can be directly introduced after multi-media filtration to remove impurities.

[0032] 2. Use chloride salts such as magnesium chloride, sodium chloride, potassium chloride, etc. to replace sulfate ions contained in the aluminum-based lithium adsorbent to reduce its influence on the performance of the aluminum-based adsorbent. No other ingredients such as weak acid need to be added to the chloride salt.

[0033] 3. The tail liquid containing sulfate ions after the column top material is replaced mainly contains chloride and a small amount of sulfate. It can be recycled by removing sulfate ions through the strong base quaternary ammonium salt anion exchange resin transformed by hydrochloric acid. This is beneficial from the perspective of environmental protection and cost.

[0034] 4. In the process of extracting lithium from ores, the adsorption method of aluminum-based lithium adsorbent is adopted to adjust the pH of lithium-containing brine leached from sulfuric acid to the range of 5 to 7. Within this range, the crystal form of aluminum-based lithium adsorbent will not change, so the performance of the adsorbent will not be affected by pH. Compared with traditional ore lithium extraction methods such as sulfate roasting, the aluminum-based lithium adsorption method has great advantages in cost and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic diagram of the preparation process of the present invention. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0037] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0038] The brine used in the embodiment is old brine after extracting potash fertilizer and pre-treated raw brine from a salt lake in South America. The ion concentrations of these two brines after multi-media filtration and impurity removal in the early stage of the experiment are shown in the following table:

[0039] Table 1 Ion content of old brine after potassium extraction from salt lake of a certain enterprise

[0040]

[0041] Table 2 Ion content of raw brine from a salt lake in South America

[0042]

[0043] In the calculation formulas for the adsorption amount, desorption amount, etc. of the aluminum-based lithium adsorbent used in the embodiments, the volume V0 of the aluminum-based lithium adsorbent used is a fixed volume before activation. Although the volume of the aluminum-based lithium adsorbent changes before and after activation, for the convenience of calculation, the aluminum-based lithium adsorbent of the present invention adopts a fixed volume before activation, and the error caused by this calculation method has limited effect on the implementation effect of the process method of the present invention.

[0044] In order to compare the performance of aluminum-based lithium adsorbents in each cycle, it is specially stipulated that the volume of water top material and the volume of salt top material in each embodiment are 1BV of the adsorbent volume V0, calculated as V1; the amount of brine used for column adsorption of lithium in each cycle remains the same as that of the first cycle V; the mixed volume of the column tail liquid in each cycle is the same as that of the first cycle V2; the amount of pure water used for analysis in each cycle is the same as that of the first cycle V3.

[0045] The aluminum-based lithium adsorbent used in the following examples is the product prepared in Example 3 of CN113578252B, and the specifications are: a columnar aluminum-based lithium adsorbent with a height of 2.5 mm and a diameter of 0.6 mm.

[0046] Embodiment 1,

[0047] First cycle adsorption:

[0048] 1. The old brine after potassium extraction in Table (1) was selected as the experimental brine and the lithium content C was measured to be 221.6 mg / L. Considering that the pH of the old brine is 5.08, the carbonate content is extremely low, and the performance of the aluminum-based lithium adsorbent is stable at pH 5.08, therefore, there is no need to perform acid or alkali adjustment steps.

[0049] 2. Use a measuring cylinder to measure V0 = 360 mL of aluminum-based lithium adsorbent and fill it into an adsorption column of appropriate specifications, keeping the filling rate no more than 80%. Then set the pure water rate to 5 BV / h to flow through the column from bottom to top to activate the aluminum-based lithium adsorbent. The activation is completed when the lithium content of the adsorption column outlet liquid is less than 20 ppm.

[0050] 3. The water layer in the adsorption column is placed flush with the activated aluminum-based lithium adsorbent layer, and then a certain volume V of the old brine in Table (1) is taken from top to bottom through the column at a flow rate of 3BV / h to extract lithium. The adsorption is completed when the lithium content of the tail liquid at the outlet of the column is measured and the lithium retention rate is less than 50%.

[0051] 4. Mix and shake the tail liquid after the column to determine the lithium content C2, which is 41.2 mg / L, and the total volume of the tail liquid mixture V2 is 5.4 L.

[0052] 5. The aluminum-based lithium adsorbent was top-loaded with pure water of volume V1 of 0.36 L, and the lithium content C1 of the top-loading liquid was measured to be 267.6 mg / L.

[0053] 6. Mix the column tail liquid to a total volume of V2, stir evenly, and use atomic absorption spectrometry to determine the mixed column tail liquid Li + Content C2, and finally the working adsorption capacity of the adsorbent is calculated using the following formula:

[0054]

[0055] Q吸 ---Lithium ion adsorption capacity, mg / mL;

[0056] C---Lithium ion content of old brine, 221.6mg / L; (Taking into account the existence of detection errors, retesting is required every cycle)

[0057] V---the volume of the old brine taken, V=V1+V2=5.76L (16BV volume of aluminum-based lithium adsorbent);

[0058] C1---Lithium ion content in water top material, 267.6 mg / L;

[0059] V1---water top material volume, 0.36L;

[0060] C2---lithium content of the column tail liquid mixture, 41.2 mg / L;

[0061] V2---the volume of the column tail liquid mixture, 5.4L;

[0062] V0---Volume of aluminum-based lithium adsorbent, 360mL.

[0063] 7. According to the total volume of 360mL of aluminum-based lithium adsorbent as 1BV, when the retention rate of lithium at the column outlet is less than 50%, the adsorption end point is reached. At this time, the mixed volume of the column tail liquid V2 = 5.4L, the lithium content C2 of the mixed column tail liquid is 41.2mg / L, the re-measured old brine lithium content C = 221.6mg / L, V = V1 + V2 = 5.76L, and the working adsorption capacity of aluminum-based lithium adsorbent for lithium is obtained by substituting into the above formula:

[0064] Q 吸 =2.66mg / mL

[0065] Analysis of the first cycle:

[0066] 8. After the adsorption is completed, the water top material returns to the original brine tank. After the adsorption is completed, pure water is used for countercurrent analysis at a flow rate of 2BV / h. When the lithium content in the desorption liquid is measured to be less than 20ppm, the desorption is completed;

[0067] 9. The total volume of the desorption solution mixture is calculated as V3 and the lithium content of the elution mixture is calculated as C3. The desorption amount of the adsorbent is calculated using the following formula:

[0068]

[0069] The analytical amount of the aluminum-based lithium adsorbent is:

[0070] Q 解 =2.3mg / mL

[0071] Among them, C3---the lithium ion content of the desorption mixed solution was measured to be 207 mg / L;

[0072] V3---Total volume of desorption mixed liquid, 4L;

[0073] 10. The resolution rate of the first cycle is:

[0074]

[0075] The total yield Y of the first cycle is:

[0076]

[0077] Among them, Q 解 ---The amount of lithium desorbed per mL of aluminum-based lithium adsorbent is 2.3 mg / mL.

[0078] V0---volume of aluminum-based lithium adsorbent, 360mL;

[0079] C---Lithium ion content of old brine, 221.6mg / L;

[0080] V---the volume of the old brine taken, 5.76L (16BV volume of aluminum-based lithium adsorbent);

[0081] Second cycle adsorption:

[0082] 1. The water layer in the adsorption column of the previous cycle was placed flush with the activated aluminum-based lithium adsorbent layer, and a certain volume V of the old brine in Table (1) was taken from top to bottom through the column at a flow rate of 3BV / h to extract lithium, and the tail liquid was collected and mixed until V2 = 5.4L, and the adsorption was stopped.

[0083] 2. Use pure water with V1 = 0.36L to carry out water top loading, and measure the lithium content C in the water top loading liquid * 1 is 298.2 mg / mL.

[0084] 3. Mix the column tail liquid with a volume of V2 = 5.4L, stir evenly, and use atomic absorption spectrometry to determine the Li content in the mixed column tail liquid. + Content C * 2 is 61.64 mg / L, and the retest table (1) old brine C * The working adsorption capacity of the aluminum-based lithium adsorbent is 220.8 mg / L. The following formula is used to calculate the working adsorption capacity of the aluminum-based lithium adsorbent:

[0085]

[0086] Q * 吸 ---Working adsorption capacity of lithium ions in the second cycle, mg / mL;

[0087] C * ---The lithium ion content of the old brine was re-measured in the second cycle, 220.8 mg / L;

[0088] V---the volume of the old brine taken, V=V1+V2=5.76L;

[0089] C * 1---Lithium ion content in water top material, 298.2 mg / L;

[0090] V1---water top material volume, 0.36L;

[0091] C * 2---Lithium content of the column tail liquid mixture, 61.64 mg / L;

[0092] V2---the volume of the column tail liquid mixture, 5.4L;

[0093] V0---Volume of aluminum-based lithium adsorbent, 360mL.

[0094] 4. The working adsorption capacity of aluminum-based lithium adsorbent lithium is:

[0095] Q * 吸 =2.31mg / mL

[0096] Second cycle analysis:

[0097] 5. After the adsorption is completed, the water top material returns to the original brine tank, and then pure water is used for countercurrent analysis at a flow rate of 2BV / h until the total volume of the desorption liquid is the same as V3 in the first cycle. After mixing the desorption liquid, stir evenly to measure the lithium content C in the desorption liquid. * 3 is 189 mg / L;

[0098] 6. Calculate the desorption amount of the adsorbent in the second cycle using the following formula:

[0099]

[0100] Among them, C * 3---The lithium ion content of the desorption mixed solution was measured to be 189 mg / L;

[0101] V3---Total volume of desorption mixed liquid, 4L;

[0102] 7. The analytical amount of the aluminum-based lithium adsorbent is:

[0103] Q * 解 =2.1mg / mL

[0104] 8. The resolution of lithium extraction in the second cycle is:

[0105]

[0106] The total yield of the second cycle is Y *for:

[0107]

[0108] Among them, Q * 解 ---The amount of lithium desorbed per mL of aluminum-based lithium adsorbent is 2.1 mg / mL.

[0109] V0---volume of aluminum-based lithium adsorbent, 360mL;

[0110] C * ---Lithium ion content of old brine, 220.8mg / L;

[0111] V---the volume of the old brine taken, 5.76L (16BV of resin volume);

[0112] The adsorption and desorption operations of the third cycle are the same as those of the previous cycle to obtain the Q of the third cycle. ** 吸 , Q ** 解 , resolution, yield Y ** They are:

[0113] Q ** 吸 =1.83mg / mL Q ** 解 =1.7mg / mL

[0114]

[0115] Y ** =48.6%

[0116] The above periodic experiments show that when the resolution rate of a certain cycle is too low and the resolution is incomplete, the adsorption amount of the next cycle will be reduced accordingly. Since the sulfate ions and lithium ions in the original brine are easily aggregated in the structure of the aluminum-based lithium adsorbent during the adsorption stage to form low-solubility lithium sulfate salts, the lithium sulfate salts block the lithium active sites on the aluminum-based lithium adsorbent, causing the adsorbent performance to decay. In this regard:

[0117] Use saturated sodium chloride salt with a volume of 1BV of aluminum-based lithium adsorbent, and carry out salt topping from bottom to top at a flow rate of 2BV / h. Collect the top liquid. After most of the sulfate radicals are removed by the strong base quaternary ammonium salt anion exchange resin, the top liquid can be used again when the next batch of aluminum-based lithium adsorbent is deactivated.

[0118] The adsorption and analysis steps of the fourth cycle are the same as the previous cycle.

[0119] Q after chloride salt top-loading in the fourth cycle *** 吸 , Q ***解 , resolution, Y *** They are:

[0120] Q *** 吸 =2.43mg / mL Q *** 解 =2.21mg / mL

[0121]

[0122] Y *** =65%

[0123] Therefore, after the aluminum-based lithium adsorbent was topped with saturated sodium chloride, the adsorption and analysis performance of the aluminum-based lithium adsorbent was improved again, and the final yield was also improved.

[0124] The analyzed lithium-containing solutions from cycles 1 to 4 were mixed, and the various ions in the analyzed mixed lithium-containing solutions were measured by ICP and ion chromatography. The results are shown in Table 3.

[0125] Table 3 Ion content in mixed lithium-containing solution

[0126]

[0127] The lithium-containing solution was concentrated by RO membrane in turn, and the concentrate was then filtered through nanofiltration membrane to remove calcium and magnesium ions, and then filtered through sodium aminocarboxylic acid chelating resin to further remove calcium and magnesium ions, and then electrodialysis was used to remove boron. After further boron removal by meglumine resin, conventional operation procedures such as MVR removal and lithium precipitation were performed. The final product was tested and analyzed, and the results are shown in Table 4.

[0128] Table 4

[0129]

[0130] The main content is 99.70%, reaching the battery grade requirement.

[0131] Example 2

[0132] First cycle adsorption:

[0133] 1. Select the raw brine from a salt lake in South America in Table (2) as the experimental brine. Considering its pH is 8.0, add industrial hydrochloric acid to adjust the pH from 5 to 7 and remove carbonate ions.

[0134] 2. Use a measuring cylinder to measure V0 = 360 mL of aluminum-based lithium adsorbent and fill it into an aluminum-based lithium adsorption column of appropriate specifications, keeping the filling rate no more than 80%. Then set the pure water rate to 5 BV / h to flow through the column from bottom to top to activate the aluminum-based lithium adsorbent. The activation is completed when the lithium content in the liquid at the outlet of the adsorption column is less than 20 ppm.

[0135] 3. The water layer in the adsorption column is placed until it is flush with the activated aluminum-based lithium adsorbent layer, and then a certain volume V of South American raw brine in Table (2) is taken from top to bottom through the column at a flow rate of 3BV / h to extract lithium. The lithium content of the tail liquid at the outlet of the column is measured until the lithium retention rate is less than 50%, which means that the adsorption is complete. The tail liquid after the column is mixed and shaken to determine the lithium content C2 is 97.65 mg / L, and the tail liquid mixed liquid volume V2 is 1.8L.

[0136] 4. The adsorbent was top-charged with pure water of volume V1 of 0.36 L, and the lithium content C1 of the top-charge liquid was measured to be 350.1 mg / L.

[0137] 5. Finally, the working adsorption capacity of the adsorbent is calculated using the following formula:

[0138]

[0139] Q 吸 ---Lithium ion adsorption capacity, mg / mL;

[0140] C--Lithium ion content of original brine, 663.8mg / L; (Taking into account the existence of detection error, retest is required every cycle)

[0141] V---the volume of the old brine taken, V=V1+V2=2.16L (6BV volume of aluminum-based lithium adsorbent);

[0142] C1---Lithium ion content in water top material, 350.1 mg / L;

[0143] V1---water top material volume, 0.36L;

[0144] C2---lithium content of the column tail liquid mixture, 97.65 mg / L;

[0145] V2---the volume of the column tail liquid mixture, 1.8L;

[0146] V0---Volume of aluminum-based lithium adsorbent, 360mL.

[0147] 6. The working adsorption capacity of aluminum-based lithium adsorbent for lithium is:

[0148] Q 吸 =3.14mg / mL

[0149] Analysis of the first cycle:

[0150] 7. After the adsorption is completed, the water top material returns to the original brine tank and is analyzed with pure water at a flow rate of 2bv / hour. When the lithium content in the desorption liquid is measured to be less than 20ppm, the desorption is completed;

[0151] 8. The total volume of the desorption solution mixture is calculated as V3 and the lithium content of the elution mixture is calculated as C3. The desorption amount of the adsorbent is calculated using the following formula:

[0152]

[0153] The analytical amount of the aluminum-based lithium adsorbent is:

[0154] Q 解 =2.83mg / mL

[0155] Among them, C3---the lithium ion content of the desorption mixed solution was measured to be 235.65 mg / L;

[0156] V3---Total volume of desorbed mixed liquid, measured as 4.32L;

[0157] 9. The lithium resolution rate in the first cycle is:

[0158]

[0159] The total yield Y of the first cycle is:

[0160]

[0161] Among them, Q 解 ---The amount of lithium desorbed per mL of aluminum-based lithium adsorbent is 2.83 mg / mL.

[0162] V0---volume of aluminum-based lithium adsorbent, 360mL;

[0163] C---Lithium ion content of old brine, 663.8mg / L;

[0164] V---the volume of the old brine taken, 2.16L (6BV volume of aluminum-based lithium adsorbent);

[0165] Second cycle adsorption:

[0166] 1. The water layer in the previous cycle adsorption column is placed flush with the activated aluminum-based lithium adsorbent layer, and a certain volume V of the raw brine in Table (2) is taken from top to bottom through the column at a flow rate of 3BV / h to extract lithium. The tail liquid is collected and mixed until V2 = 1.8L, and the adsorption is stopped.

[0167] 2. Use pure water with V1 = 0.36L to carry out water top loading, and measure the lithium content C in the water top loading liquid * 1 is 380.6 mg / mL.

[0168] 3. Mix the column tail liquid with a volume of V2 = 1.8L, stir evenly, and use atomic absorption spectrometry to determine the Li content in the mixed column tail liquid. + Content C *2 is 212.08 mg / L, and the retest table (2) old brine C * The working adsorption capacity of lithium adsorbent is 678.5 mg / L. The following formula is used to calculate the working adsorption capacity of lithium adsorbent:

[0169]

[0170] Q * 吸 ---Working adsorption capacity of lithium ions in the second cycle, mg / mL;

[0171] C * ---The lithium ion content of the old brine was re-measured in the second cycle, 678.5 mg / L;

[0172] V---the volume of the old brine taken, V=V1+V2=2.16L;

[0173] C * 1---Lithium ion content in water top material, 380.6 mg / L;

[0174] V1---water top material volume, 0.36L;

[0175] C * 2---Lithium content of column tail liquid mixture, 212.08 mg / L;

[0176] V2---the volume of the column tail liquid mixture, 1.8L;

[0177] V0---Volume of aluminum-based lithium adsorbent, 360mL.

[0178] 4. The working adsorption capacity of aluminum-based lithium adsorbent lithium is:

[0179] Q* 吸 =2.63mg / mL

[0180] Second cycle analysis:

[0181] 5. After the adsorption is completed, pure water is used for countercurrent analysis at a flow rate of 2BV / h until the total volume of the analytical solution is the same as V3 in the first cycle. After mixing the analytical solutions, stir evenly to measure the lithium content C*3 in the desorption solution to be 168.33 mg / L;

[0182] 6. The analytical amount of the aluminum-based lithium adsorbent in the second cycle is calculated using the following formula:

[0183]

[0184] Among them, C*3---the lithium ion content of the desorption mixed solution was measured to be 168.33 mg / L;

[0185] V3---Total volume of desorption mixed liquid, 4.32L;

[0186] 7. The analytical amount of the aluminum-based lithium adsorbent is:

[0187] Q* 解 =2.02mg / mL

[0188] 8. The resolution of lithium extraction in the second cycle is:

[0189]

[0190] The total yield Y* of the second cycle is:

[0191]

[0192] Among them, Q* 解 ---The amount of lithium analyzed per mL of aluminum-based lithium adsorbent is 2.02 mg / mL.

[0193] V0---volume of aluminum-based lithium adsorbent, 360mL;

[0194] C*---The lithium ion content of old brine was retested in the second cycle, 678.5 mg / L;

[0195] V---the volume of the old brine taken, 2.16L (6BV volume of aluminum-based lithium adsorbent);

[0196] The adsorption and analysis operations of the third cycle are the same as those of the previous cycle.

[0197] Get Q** of the third cycle 吸 、Q** 解 , resolution rate, and Y** are:

[0198] Q ** 吸 =1.42mg / mL Q ** 解 =1.33mg / mL

[0199]

[0200] Y ** =33.06%

[0201] The above-mentioned experiments show that the performance of the aluminum-based lithium adsorbent decays significantly with the periodic increase. This is because the sulfate radicals and lithium ions in the original brine are easily aggregated in the structure of the aluminum-based lithium adsorbent during the adsorption stage to form low-solubility lithium sulfate salts. The lithium sulfate salts block the lithium active sites on the aluminum-based lithium adsorbent, causing the adsorbent performance to decay. In this regard:

[0202] A 10% magnesium chloride salt solution with a volume of 1BV of aluminum-based lithium adsorbent is used to carry out salt topping from bottom to top at a flow rate of 2BV / h, and the top liquid is collected. After passing through the sulfate-removing resin, the salt top liquid can be used as the top material again when the aluminum-based lithium adsorbent is deactivated next time.

[0203] The adsorption and analysis steps of the fourth cycle are the same as the previous cycle.

[0204] Q*** after chloride salt top-loading in the fourth cycle 吸 , Q*** 解 , resolution rate, and Y*** are:

[0205] Q *** 吸 =2.76mg / mL Q *** 解 =2.59mg / mL

[0206]

[0207] Y *** =64%

[0208] Therefore, after the adsorbent was salt-topped with 10% magnesium chloride, the performance of the aluminum-based lithium adsorbent was activated and improved again, and the lithium yield was improved.

[0209] The analyzed lithium-containing solutions from the above cycles were mixed, and the various ions in the analyzed mixed lithium-containing solutions were measured by ICP and ion chromatography. The results are shown in Table 5.

[0210] Table 5 Ion content in mixed lithium-containing solution

[0211]

[0212] The lithium-containing solution was concentrated by RO membrane in turn, and the concentrate was then filtered through nanofiltration membrane to remove calcium and magnesium ions, and then filtered through sodium aminocarboxylic acid chelating resin to further remove calcium and magnesium ions, and then electrodialysis was used to remove boron. After further boron removal by meglumine resin, conventional operation procedures such as MVR removal and lithium precipitation were performed. The final product was tested and analyzed, and the results are shown in Table 6.

[0213] Table 6

[0214]

[0215] The main content is 99.62%, reaching the battery grade requirement.

[0216] In summary, the working adsorption capacity of the aluminum-based lithium adsorbent in Examples 1 and 2 is generally greater than its desorption capacity. This is because some lithium ions in the brine are embedded in the aluminum-based lithium adsorbent in the form of low-solubility sulfate, causing the lithium active sites on the aluminum-based lithium adsorbent to be blocked, ultimately leading to the performance attenuation of the aluminum-based lithium adsorbent. After the deactivated aluminum-based lithium adsorbent is salted with a certain concentration of chloride salt, the performance of the aluminum-based lithium adsorbent can be restored to a certain level.

[0217] Although some embodiments have been shown and described in the present invention, it is impossible to list all the embodiments one by one. For those skilled in the art, it can be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. However, these measures are all within the scope of protection of the present invention and are defined by the attached claims and their equivalents.

Claims

1. A method for extracting lithium from sulfate-containing brine, comprising the following steps: Step S1. Selecting brine containing sulfate, filtering and removing impurities to obtain brine with a pH value of 5 to 7, or adjusting the pH value of the brine to 5 to 7 with acid or alkali; Step S2. Passing the brine treated in step S1 through a resin column containing an aluminum-based lithium adsorbent for column adsorption to extract lithium ions from the brine; Step S3. After the adsorption is completed, the aluminum-based lithium adsorbent after the lithium extraction in step S2 is eluted with pure water, countercurrent analyzed, and the lithium-containing liquid A is collected and analyzed; Repeating steps S2 and S3 until the adsorption capacity of the aluminum-based lithium adsorbent drops to 70% or less of the initial capacity; Step S4. using soluble chloride salt to replace sulfate ions contained in the aluminum-based lithium adsorbent after lithium extraction, and then analyzing it with pure water to obtain an analyzed lithium-containing liquid B; combining the analyzed lithium-containing liquid A and the analyzed lithium-containing liquid B to obtain a mixed analyzed lithium-containing liquid.

2. The method according to claim 1, characterized in that: In step S1, the brine is salt lake brine containing sulfate and / or ore leaching brine containing sulfate; And / or, in step S1, the mass concentration of sulfate ions in the brine is 6% to 50% of the mass concentration of chloride ions.

3. The method according to claim 1, characterized in that: In the step S2, the aluminum-based lithium adsorbent needs to be activated before use, and the activation method is as follows: flushing through the column with deionized water until the lithium ion content at the outlet of the resin column containing the aluminum-based adsorbent reaches the activation end point within 20 ppm.

4. The method according to claim 1, characterized in that: In the step S2, the adsorption is completed when the lithium content in the tail liquid at the outlet of the column is measured to a lithium retention rate of less than 50%, wherein the retention rate refers to the mass concentration of lithium contained in the tail liquid after the pretreated raw halide passes through the aluminum-based lithium adsorption column, which accounts for the mass concentration of lithium contained in the tail liquid before the raw halide enters the column.

5. The method according to claim 1, characterized in that: In step S4, the soluble chloride salt is selected from: magnesium chloride, sodium chloride, lithium chloride, potassium chloride or a mixture of two thereof.

6. The method according to claim 1, characterized in that: In the step S4, the soluble chloride salt is used in the form of an aqueous solution, and the mass concentration of the soluble chloride salt is 6% to 26.5%.

7. The method according to claim 1, characterized in that: The method further comprises the following step S5: removing impurities and RO concentration from the mixed analytical lithium-containing liquid by using a membrane combination and a resin system, and then performing MVR and lithium precipitation treatment to obtain lithium carbonate with a main content reaching battery grade.

8. The method according to claim 7, characterized in that: In step S5, the membrane combination is selected from at least two of the following membranes for membrane combination treatment: hollow fiber membrane, ceramic membrane, nanofiltration membrane, RO reverse osmosis membrane, bipolar membrane electrodialysis; And / or, the resin is selected from at least one of the following resins: calcium and magnesium chelate resins, and chelate resins specifically for boron removal.

9. The method according to any one of claims 1 to 8, characterized in that: The method further comprises the following step S6: removing sulfate from the salt top material replacement liquid containing sulfate obtained in step S4 through a strong base anion exchange resin, and then collecting the chloride-containing replacement liquid after the sulfate is removed for recycling to replace the sulfate on the next batch of deactivated aluminum-based lithium adsorbents.

10. The method according to claim 9, characterized in that: The strong base anion exchange resin described in step S6 is a strong base quaternary ammonium salt anion exchange resin, which needs to be converted into a chlorine type by hydrochloric acid with a mass concentration of 4% before use, and then washed with pure water until the pH value of the water outlet is close to neutral before use.

Citation Information

Cited By

  • Method for co-production of lithium and potassium in salt lake brine

    CN121823616A

  • Pretreatment method and device for aluminum-based adsorbent poisoning factors in lithium-containing brine

    CN122503659A